Crystal structure and Hirshfeld surface analysis of 1-(tert-butylamino)-3-mesitylpropan-2-ol hemihydrate - Ali N. Khalilov; Victor N. Khrustalev; Tatiana A. Tereshina; Mehmet Akkurt; Rovnag M. Rzayev; Anzurat A. Akobirshoeva; İbrahim G. Mamedov (Acta Crystallographica Section E: Crystallographic Communications, 2022)
The title compound, 2C16H27NO·H2O, crystallizes in the monoclinic P21/c space group with two independent molecules (A and B) in the asymmetric unit. In the crystal, molecules A and B are linked through the water molecules by intermolecular O—H...O and O—H...N hydrogen bonds, producing chains along the b-axis direction. These chains are linked with neighboring chains parallel to the (103) plane via C—H...π interactions, generating ribbons along the b-axis direction. The stability of the molecular packaging is ensured by van der Waals interactions between the ribbons. According to the Hirshfeld surface study, H...H interactions are the most significant contributors to the crystal packing (80.3% for molecule A and 84.8% for molecule B).